A Study on Occupational Stress of Working Women- Special Reference to Government Schools, Divisional Secretariat, and Hospital (American Journal of Interdisciplinary Research and Innovation, 2023)
Working women are often forced to take on multiple duties, such as working at home, and at the workplace, which can lead to stressful situations. They are also conditioned to be more obedient, fearful, and incapable of dealing with obstacles, leading to a foundation for stress. The primary objective of the study is to examine the level of occupational stress of working women attached to government schools, divisional secretariat, and hospital. A total of 120 working women were chosen at random from government schools (40), divisional secretariat (40), and hospital (40) in Nintavur which is situated in Ampara district of Sri Lanka. The measuring tool was modified questionnaire developed by Aroosiya and Ali (2016), consisting of 24 questions. This research is based on two hypotheses; Working women attached to government schools, divisional secretariat, and hospital in Nintavur do have occupational stress; There is significant difference between the occupational stress of working women attached to government schools, divisional secretariat, and hospital in Nintavur based on demographic variables. Descriptive statistics were applied to the data. The study’s findings revealed that the level of occupational stress among working women at Nintavur’s government schools, divisional secretariat, and hospital was moderate level. Moreover, the employees attached to Divisional Secretariat, Government School, and Hospital have the moderate mean score by comparing the demographic variable “Working Station”. Further, Management Service Officers has the highest mean score by comparing the demographic variable “Type of Position”.